Treatment of asymptomatic tuberculosis: Protocol for a systematic review of treatment strategies, regimens, and clinical outcomes - Yang Li; Ammar Saad; Zhen Feng; Shijia Ge; Lingyun Song; Yanfei Ren; Yan Miao; Ting Li; Tingting Zhao; Wenting Huang; Jiqin Wu; Feng Sun; et al. (PLoS ONE, 2026)
Introduction Asymptomatic tuberculosis (TB) is increasingly recognised through active case finding and prevalence surveys. However, treatment strategies for this patient group remain poorly defined, and there is no consensus on optimal regimens, duration, or outcomes. Methods and analysis We will conduct a systematic review of observational and interventional studies reporting anti-TB treatment in patients with asymptomatic TB. Databases including MEDLINE, Embase, Scopus, Web of Science, CINAHL, and the Cochrane Library will be searched without language restrictions. Outcomes of interest include favourable outcome rate, treatment coverage, success rate, relapse, mortality, loss to follow-up, adverse events, and patient-reported outcomes such as pill burden and treatment discontinuation. Study selection, data extraction, and quality assessment will be performed independently by two reviewers, following PRISMA guidelines. Where appropriate, meta-analyses will be conducted using a random-effects model. Discussion This review will provide a comprehensive synthesis of current evidence on the treatment of asymptomatic TB. It aims to inform future clinical and public health strategies, including the potential for simplified or shortened treatment regimens tailored to this population. By identifying gaps and inconsistencies in current practice, the findings will support evidence-based decision-making and contribute to global TB control efforts.